2005
DOI: 10.1074/jbc.m412148200
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Phosphoinositide 3-Kinase Defines a Positive Contribution of Tyrosine Kinase Signaling to E-cadherin Function

Abstract: Classical cadherin adhesion molecules can function as adhesion-activated cell-signaling receptors. One key target for cadherin signaling is the lipid kinase phosphoinositide (PI) 3-kinase, which is recruited to cell-cell contacts and activated by E-cadherin. In this study, we sought to identify upstream factors necessary for E-cadherin to activate PI 3-kinase signaling. We found that inhibition of tyrosine kinase signaling blocked recruitment of PI 3-kinase to E-cadherin contacts and abolished the ability of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Such E-cadhactivated PI3K cascade has a clear impact on cadh function, as it is required for adhesive strengthening and for the efficient assembly of cadh-based adhesive contacts. More recently, there is evidence that upstream signaling from RTKs and src family kinases upregulates adhesive cadherin function (Pang et al, 2005;.…”
Section: Discussionmentioning
confidence: 99%
“…Such E-cadhactivated PI3K cascade has a clear impact on cadh function, as it is required for adhesive strengthening and for the efficient assembly of cadh-based adhesive contacts. More recently, there is evidence that upstream signaling from RTKs and src family kinases upregulates adhesive cadherin function (Pang et al, 2005;.…”
Section: Discussionmentioning
confidence: 99%
“…This is intriguing in light of reports that depending on context, PI3-kinase signalling can play positive or negative roles in the formation of E-cadherin-based adherens junctions. Thus, while PI3-kinase signalling enhances the formation of nascent adhesive contacts following E-cadherin homophilic ligation (Kovacs et al, 2002;Pang et al, 2005), in v-Src-expressing MDCK cells it promotes junctional instability, since cell-cell aggregation can be induced in an E-cadherin-dependent manner by expressing PTEN (Kotelevets et al, 2001). These contrasting effects are probably explained by marked differences in signal strength and duration.…”
Section: Functional Co-operation Between Gab2 and Src Hl Bennett Et Almentioning
confidence: 92%
“…Many studies have demonstrated that tyrosine kinase activity is necessary for the assembly of AJ and the interaction of PI3K with the E-cadherin-catenin complex. Pharmacological inhibition of tyrosine kinase perturbs the formation of AJ and prevents activation of PI3K by Ca 2ϩ o (16,22,23). In differentiating mouse keratinocytes, Ca 2ϩ o -induced assembly of E-cadherin-catenin complex and the recruitment of PI3K to E-cadherin are accompanied by tyrosine phosphorylation of ␤-, ␥-, and p120-catenin (22).…”
Section: ؉mentioning
confidence: 99%